First record of Jugatala cribelliger = Mycobates (Calyptozetes) cribelliger (Berlese, 1904) (Acari: Oribatida) in the Romanian fauna - IOANA NAE; MARK MARAUN (Travaux de l'Institut de Speologie Emile Racovitza, 2024)
The authors present one oribatid mite species new for the Romanian fauna, found in Piatra Craiului Mountains. Jugatala cribelliger = Mycobates (Calyptozetes) cribelliger (BERLESE, 1904) is described using scanning electronic microscope images, with notes on its morphology, taxonomic status and distribution.